Wild-type SARS-CoV-2 neutralizing immunity decreases across variants and over time but correlates well with diagnostic testing - O’Shea, Kelly M.; Schuler, Charles F.; Chen, Jesse; Troost, Jonathan P.; Wong, Pamela T.; Chen, Kelsea; O’Shea, Daniel R.; Peng, Westley; Gherasim, Carmen; Manthei, David M.; Valdez, Riccardo; Baldwin, James L.; et al. (Frontiers in Immunology, 2023)
Importance The degree of immune protection against severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) variants provided by infection versus vaccination with wild-type virus remains unresolved, which influences future vaccine boosters. One modality for assessing immune protection is viral neutralization; however, few studies involve a large-scale analysis of viral neutralization against the Omicron variant by sera from individuals infected with wild-type virus. Objectives 1) To define the degree to which infection versus vaccination with wild-type SARS-CoV-2 produced neutralizing antibodies against subsequent variants, including Omicron. 2) To determine whether clinically available data, such as infection/vaccination timing or antibody status, can predict variant neutralization. Results Vaccination after prior infection led to the highest neutralization titers at all timepoints for all variants. Neutralization was more durable in the setting of prior infection versus only vaccination. Standard spike antibody clinical testing effectively predicted neutralization for wild-type and Delta. However, nucleocapsid antibody presence was the best independent predictor of Omicron neutralization. Neutralization of Omicron was lower than both wild-type and Delta across all groups and timepoints, with significant activity only present in patients that were first infected and later immunized. Conclusions Participants having both infection and vaccination with wild-type virus had the highest neutralizing antibody levels against all variants and had persistence of activity. Neutralization correlated with spike antibody levels against wild-type and Delta variants but Omicron neutralization better correlated with evidence of prior infection. These data help explain why ‘breakthrough’ Omicron infections occurred in previously vaccinated individuals and suggest better protection is observed in those with both vaccination and previous infection. This study also supports the concept of future SARS-CoV-2 Omicron-specific vaccine boosters.